2021
DOI: 10.3389/fgene.2021.674534
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the Single Human Chromosome 18 as a “Gold Standard” for Its Transcriptome

Abstract: The cutoff level applied in sequencing analysis varies according to the sequencing technology, sample type, and study purpose, which can largely affect the coverage and reliability of the data obtained. In this study, we aimed to determine the optimal combination of parameters for reliable RNA transcriptome data analysis. Toward this end, we compared the results obtained from different transcriptome analysis platforms (quantitative polymerase chain reaction, Illumina RNASeq, and Oxford Nanopore Technologies Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…We found that both Illumina and ONT showed good concordance between replicates, while the former platform performed better. This finding is in line with previous results [ 6 , 42 ]. The gene ranks correlation between both platforms was also relatively high, while there were genes whose expression was detected only by one of them.…”
Section: Discussionsupporting
confidence: 94%
“…We found that both Illumina and ONT showed good concordance between replicates, while the former platform performed better. This finding is in line with previous results [ 6 , 42 ]. The gene ranks correlation between both platforms was also relatively high, while there were genes whose expression was detected only by one of them.…”
Section: Discussionsupporting
confidence: 94%
“…It should also be taken into account that different sequencing platforms have advantages and disadvantages. Therefore, a combination of several of them may be needed for a comprehensive analysis of gene expression [125]. Besides, computational models [126], such as ML, have been applied to these studies [127], including dimension reduction methods [128].…”
Section: Functional Genomicsmentioning
confidence: 99%
“…Several platforms recently became commercially available such as Helicos Bio Sensing, Pacific Biosciences, BGI Group Complete Genomics, and Oxford Nanopore Technology. Each platform has its own advantages and disadvantages (Blom 2021;Broseus et al 2020), Thus, a multifold compound of them may be required for a deep analysis of gene phraseology (Ilgisonis et al 2021). In addition, computational models like machine learning have been exerted to these analyses (Bobrovskikh et al 2021;Liu et al 2021).…”
Section: Third Generationmentioning
confidence: 99%